Évaluation des risques écologiques : développements prioritaires et recherches concomitantes - Yves Perrodin (VertigO, 2012)
At the opposite of the health risk assessment, the Ecological Risk Assessment (ERA) is still in its early stages internationally. Nevertheless, the need for this type of tool for decision support is huge in many areas (impact assessment of industrial sites, management of polluted sites and urban wastelands, transport infrastructure design, sustainable urban development,...). To address these needs, some countries have worked in order to develop their own approaches. In these countries, the development and optimization of these have involved many actors, acting both within government agencies, and within academia. This prospective paper, after a synthesis of existing ERA methodologies, deals with researches necessary to advance each stage of the ERA, namely "the problem formulation", "the assessment of exposure of ecosystems", "the assessment of effects on ecosystems, and "the ecological risk assessment itself".